Nonalcoholic fatty liver disease in inflammatory arthritis: Relationship with cardiovascular risk - Barbarroja, Nuria; Ruiz-Ponce, Miriam; Cuesta-López, Laura; Pérez-Sánchez, Carlos; López-Pedrera, Chary; Arias-de la Rosa, Iván; Collantes-Estévez, Eduardo (Frontiers in Immunology, 2022)
Liver disease is one of the most important causes of morbidity and mortality worldwide whose prevalence is dramatically increasing. The first sign of hepatic damage is inflammation which could be accompanied by the accumulation of fat called non-alcoholic fatty liver disease (NAFLD), causing damage in the hepatocytes. This stage can progress to fibrosis where the accumulation of fibrotic tissue replaces healthy tissue reducing liver function. The next stage is cirrhosis, a late phase of fibrosis where a high percentage of liver tissue has been replaced by fibrotic tissue and liver functionality is substantially impaired. There is a close interplay of cardiovascular disease (CVD) and hepatic alterations, where different mechanisms mediating this relation between the liver and systemic vasculature have been described. In chronic inflammatory diseases such as rheumatoid arthritis (RA) and psoriatic arthritis (PsA), in which the CVD risk is high, hepatic alterations seem to be more prevalent compared to the general population and other rheumatic disorders. The pathogenic mechanisms involved in the development of this comorbidity are still unraveled, although chronic inflammation, autoimmunity, treatments, and metabolic deregulation seem to have an important role. In this review, we will discuss the involvement of liver disease in the cardiovascular risk associated with inflammatory arthritis, the pathogenic mechanisms, and the recognized factors involved. Likewise, monitoring of the liver disease risk in routine clinical practice through both, classical and novel techniques and indexes will be exposed. Finally, we will examine the latest controversies that have been raised about the effects of the current therapies used to control the inflammation in RA and PsA, in the liver damage of those patients, such as methotrexate, leflunomide or biologics.